(3GdeSQY eNJUQ GdeeJY (B( (3aj Yde GdLHQ (B)s - (3CHi GdYHGS CMeO Hf eMeO Hf Ydj GdeYQha HGHf GdgGFes; (3TgGH GdOjf CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,J (B815 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO ddg aGdZQV GNJUGQ (B" (3GdeeJY (B" (3hJSejI eNJUQI (B" (3HGdeSQY (B" (3djSgd Ydief bUQJ geJg hChd GdefXheI (B: (3HMeO Edgi CHJOi eG CMGhd hCgOi UdGI eY SdGe HTGcd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B41 - (3U(B95s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B226s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B125 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B84 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs